2022
DOI: 10.3390/s22249735
|View full text |Cite
|
Sign up to set email alerts
|

A Heterogeneous Ensemble Approach for Travel Time Prediction Using Hybridized Feature Spaces and Support Vector Regression

Abstract: Travel time prediction is essential to intelligent transportation systems directly affecting smart cities and autonomous vehicles. Accurately predicting traffic based on heterogeneous factors is highly beneficial but remains a challenging problem. The literature shows significant performance improvements when traditional machine learning and deep learning models are combined using an ensemble learning approach. This research mainly contributes by proposing an ensemble learning model based on hybridized feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The ensemble learning models have been explored due to their high efficiency; several architectures based on this approach have been used for time series forecasting, such as the cooperative [33], stacking [34], heterogeneous [35], bagging [36], boosting [37], random subspace [38], and random forest [39] ensemble learning models. The advantage of this approach is the combination of simpler models to build a stronger model [40], which has a high predictive ability and can be more efficient than models based on deep learning.…”
Section: Related Workmentioning
confidence: 99%
“…The ensemble learning models have been explored due to their high efficiency; several architectures based on this approach have been used for time series forecasting, such as the cooperative [33], stacking [34], heterogeneous [35], bagging [36], boosting [37], random subspace [38], and random forest [39] ensemble learning models. The advantage of this approach is the combination of simpler models to build a stronger model [40], which has a high predictive ability and can be more efficient than models based on deep learning.…”
Section: Related Workmentioning
confidence: 99%
“…Subsequently, scholars [30] proposed a neural network model called ACBiGRU and applied it to short-term traffic flow prediction, embedding attention mechanisms in convolutional neural networks to focus on convolutional layer results with distinct weights, effectively extracting the spatial features of traffic flow. Chughtai et al [31] observed a substantial enhancement in predictive accuracy through the utilization of ensemble learning to amalgamate conventional machine learning and deep learning models.…”
Section: Introductionmentioning
confidence: 99%